The effect of acupressure on pain level and hemodynamic parameters after coronary angiography: a randomized controlled study - Düzel, Barış; Çam Yanik, Tuğba; Kanat, Canan; Altun Uğraş, Gülay (Frontiers in Cardiovascular Medicine, 2023)
Background: Subsequent to coronary angiography, procedures performed to prevent bleeding may cause pain in the patient. In this study, the effect of acupressure on pain level and hemodynamic parameters in patients undergoing coronary angiography was aimed to be determined. Method: In this prospective, two-arm (1:1), randomized controlled trial, 124 patients undergoing coronary angiography were included. The randomly assigned study group (n=62) received acupressure on LI4 (on the dorsum of the hand, between the 1st and 2nd metacarpal bones), PC6 (three fingers above the wrist), and LI11 (at the lateral end of the transverse cubital crease) points for 15 minutes at 2 hours after angiography, while the control group (n=62) received no acupressure. Data were collected using the Visual Pain Scale (VAS) and hemodynamic parameters [systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate (HR), respiratory rate (RR), and peripheral oxygen saturation (SpO2)] monitoring form before, immediately after, at 10 min, 20 min, and 30 min after acupressure. Results: In the study, it was found that patients had moderate pain after coronary angiography (study group: 5.02±2.27; control group: 3.98±1.82). When the groups were compared, it was found that the VAS score of the study group before angiography was significantly higher than the control group, but it was lower than the control group immediately after acupressure, at 10 minutes, 20 minutes, and 30 minutes acupressure. In addition, it was determined that acupressure was significantly higher in DBP and RR in the study group compared to the control group at the 20th and 30th min; it was not effective in SBP, HR, and SpO2 values. Conclusion: The results of the study indicated that patients reported moderate pain after coronary angiography, and acupressure was effective in reducing the pain level, but it affected only DBP and RR among hemodynamic parameters.Since the study was single-centered and followed for a short time, it is recommended to conduct new studies with a longer duration.